Liquid metal polymer composites: from printed stretchable circuits to soft actuators - Majidi, Carmel; Alizadeh, Kaveh; Ohm, Yunsik; Silva, Andre; Tavakoli, Mahmoud (Flexible and printed electronics, 2022)
Soft polymers embedded with liquid metals like eutectic gallium-indium (EGaIn) exhibit unique combinations of mechanical, electrical, and thermal properties that are not possible with other material systems. For example, a soft silicone elastomer embedded with a percolating network of EGaIn microdroplets can function as a highly soft and elastic conductor that can be stretched to 600% strain without significant change in electrical resistance. Depending on the choice of polymer matrix and EGaIn microstructure, these soft material composites can be engineered to exhibit mechanical and electrical self-healing properties as well as high fracture toughness and resistance to tearing. Moreover, when solid filler particles like silver flakes are added to EGaIn-polymer composites, they can function as printable conductive inks that are fully elastic, non-marking, and non-smearing when cured. In this short review, we present different classes of EGaIn-polymer composites, discuss approaches to materials synthesis and patterning, and compare their properties with other material systems. Additionally, we will review applications of this emerging class of materials in domains ranging from wearable bioelectronics to soft robotics, shape programmable smart materials, as well as energy storage and harvesting devices.